2021
DOI: 10.1038/s41598-021-85337-9
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of polyunsaturated fatty acids (PUFAs) and aerobic exercise improve functioning, morphology, and redox balance in prostate obese rats

Abstract: The high-fat diet (HFD) stimulates an increase in lipids and can be prejudicial for harmful to prostatic morphogenesis. Polyunsaturated fatty acid (PUFAs) have anti-inflammatory and antioxidant action in some types of cancer. The combination of aerobic physical exercise and PUFA can be more effective and reduce the risk of death. The study evaluates the effects of aerobic physical exercise associated with omega-3 (fish and chia oils), on the ventral prostate of Wistar rats those fed with HFD. Here, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…In Apo E knockout mice, the fish oil-rich diet increased NO production and endothelial NO synthase (NOS) expression and lowered the expression of p22 phlox and O2-generation (16). Moreover, ω-3 PUFAs may increase antioxidant activity, such as superoxide dismutase (SOD), guaiacol peroxidase (GPX), catalase (CAT), and glutathione (GSH), enhancing the resistance to free radical attack and reducing lipid peroxidation and oxidative stress (17)(18)(19). Diet with a 1:1 ratio of EPA/DHA improved the oxidative stress parameters (SOD and GPX in erythrocytes) and plasma antioxidant capacity (19).…”
Section: Anti-oxidation and Improved Endothelial Functionmentioning
confidence: 99%
“…In Apo E knockout mice, the fish oil-rich diet increased NO production and endothelial NO synthase (NOS) expression and lowered the expression of p22 phlox and O2-generation (16). Moreover, ω-3 PUFAs may increase antioxidant activity, such as superoxide dismutase (SOD), guaiacol peroxidase (GPX), catalase (CAT), and glutathione (GSH), enhancing the resistance to free radical attack and reducing lipid peroxidation and oxidative stress (17)(18)(19). Diet with a 1:1 ratio of EPA/DHA improved the oxidative stress parameters (SOD and GPX in erythrocytes) and plasma antioxidant capacity (19).…”
Section: Anti-oxidation and Improved Endothelial Functionmentioning
confidence: 99%
“…Studies on the combined effects of antioxidant-based nutritional supplements and exercise training on the redox status are not unequivocal. In both healthy and pathological rodent models, some studies found beneficial and synergistic effects [68], but not others [69]. Moreover, some studies demonstrated that their combination attenuates and blunts their individual actions [70].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, maternal DHA supplementation during pregnancy is associated with decreased infant fat mass and increased lean body mass [ 13 ]. DHA and Eicosapentaenoic Acid (EPA) activate PPAR-α, which can inhibit expression of pro-inflammatory markers [ 14 ]. However, the potential influence of both maternal aerobic exercise and maternal polyunsaturated fatty acids (PUFAs) concentrations on infant body composition remains unknown.…”
Section: Introductionmentioning
confidence: 99%